2019
DOI: 10.18697/ajfand.85.18035
|View full text |Cite
|
Sign up to set email alerts
|

Available food options at local shops in relation to food insecurity among older adults in Sharpeville, South Africa

Abstract: Due to limited resources and complex food access systems in urban areas, especially older adults are more vulnerable to poor dietary intake and food insecurity in low-income areas in South Africa. This study assessed the prevalence of food insecurity among the older adults and explored the availability of healthy foods in local shops. It was a crosssectional study conducted in an eldercare centre in Sharpeville, South Africa with an estimated representative sample of 88 participants. Validated tools were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The high rate of divorce, unemployment, HIV/AIDS-related death, out-of-marriage child-bearing, and teenage pregnancy in South Africa often result in the grandmothers stepping in to play an additional role as caregivers to their grandchildren in addition to supporting their adult children [ 50 ]. Although we did not show any differences between the food-secure and -insecure groups, earlier studies in South Africa have shown that being a recipient of a pension, financially supporting household members, especially children, and household size (number of people in the household), were all positively associated with food insecurity status of the grandmothers [ 10 , 32 ]. The current study shows that food-insecure women were from a higher housing density and used coping strategies (borrowing money more frequently, and eating less so that others, especially children in the household had enough food to eat) when compared to the food secure women.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…The high rate of divorce, unemployment, HIV/AIDS-related death, out-of-marriage child-bearing, and teenage pregnancy in South Africa often result in the grandmothers stepping in to play an additional role as caregivers to their grandchildren in addition to supporting their adult children [ 50 ]. Although we did not show any differences between the food-secure and -insecure groups, earlier studies in South Africa have shown that being a recipient of a pension, financially supporting household members, especially children, and household size (number of people in the household), were all positively associated with food insecurity status of the grandmothers [ 10 , 32 ]. The current study shows that food-insecure women were from a higher housing density and used coping strategies (borrowing money more frequently, and eating less so that others, especially children in the household had enough food to eat) when compared to the food secure women.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to other studies in low-income communities in Africa in which food-insecure households were more likely to rely on informal food outlets, probably because food could be purchased on credit [ 13 , 43 ], all participants in the current study shopped in supermarkets due to their affordability [ 10 ]. Most women in the current study had access to a refrigerator in their homes (98.2%), which enabled them to preserve perishable products and this may explain the discrepancy in results between studies.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…11 Furthermore, in a recent study, Saha and co-authors showed that 23.8% of participants at the same senior centre in Sharpeville did not consume any milk or milk products in a day before the survey. 143 In addition, a study undertaken in Umlazi among older adults found no milk or milk products appearing in the top 20 most commonly consumed food items. This result was confirmed by 99.5% of the women and 98.0% of the men having inadequate calcium intakes.…”
Section: Animal Protein Consumption Among the Elderly In South Africamentioning
confidence: 99%